Danish GPs' Experiences When Managing Patients Presenting to General Practice with Symptoms of Acute Lower Respiratory Tract Infections: A Qualitative Study - Lise Bisgaard; Camilla Aakjær Andersen; Morten Sig Ager Jensen; Lars Bjerrum; Malene Plejdrup Hansen (MDPI AG, 2021)
One of the most common indications for antibiotic prescribing in general practice is acute lower respiratory tract infections (LRTI). This study aimed to explore general practitioners' (GPs') considerations and experiences when managing patients with symptoms of an acute LRTI. Individual semi-structured interviews were conducted with seven GPs in the North Denmark Region from January to March 2020. Data were analysed by means of systematic text condensation. The analysis revealed four themes: (1) practicalities of assessing patients with LRTI, (2) assessment of the patient, (3) treatment decisions, and (4) patient expectations. The GPs described having developed individual diagnostic strategies and routines when managing patients with symptoms of an acute LRTI. However, a general assessment of the patient was essential to all the GPs and the diagnosis was seldom based on a single symptom or finding. Most GPs described having great faith in abnormal lung auscultation. The use of C-reactive protein testing served several purposes, such as deciding on the severity of the infection, prescribing antibiotics or not, and as a communicative tool. Diagnostic uncertainty is a driver of antibiotic use and clinical practice might benefit from the development of clinical prediction rules for diagnosing pneumonia.